Development of universal device for determining the needle stroke in diesel and marine diesel sprayers - L. Yu. Volkova (Омский научный вестник)
The main malfunctions of diesel and marine diesel injectors with an increase in the needle stroke by more than 50 % of the standard value are described — an increase in the temperature of the nozzle of the sprayer, a breakthrough of cylinder gases into the cavity of the sprayer and the formation of coke, a decrease in the pressure of the injected fuel. A method is proposed for determining the maximum stroke of the needle by measuring the length of the needle shank and its conditional reduction when the needle is placed on the saddle. The device and the principle of operation of the device for determining the maximum stroke of the spray needle are shown. Drawings of the main parts of the universal device for determining the needle stroke of sprayers with a diameter from 8 to 18 mm of diesel and marine diesel engines have been developed, a prototype is made. The method of determining the motion (stroke) of the needle of the spray nozzles of diesel engines using the developed device is given.